(NhLEB(B: [(NrOMAN(B]; s (NrASSKAZY I SKAZKI DLQ DETEJ (B/ s (N~ASTX (B6s - (NmAMIN(B-(NsIBIRQK d(B. (Nn(B.s ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1981)
(Nw [ESTOJ TOM WO[LI ROMAN (B"(NhLEB(B" (NI (B"(NrASSKAZY I SKAZKI DLQ DETEJ(B".s
rus
Keywords: (NpSIHOLOGI^ESKIJ ROMANs; (NsOCIALXNYJ ROMANs -- (NrASSKAZYs -- (NsKAZKIs